2017
DOI: 10.18632/oncotarget.19491
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of macrolides, fusidic acid and mupirocin resistance among Staphylococcus aureus clinical isolates

Abstract: As an increasingly common cause of skin infections worldwide, the prevalence of antibiotic-resistant Staphylococcus aureus (S. aureus) across China has not been well documented. This literature aims to study the resistance profile to commonly used antibiotics, including macrolides, fusidic acid (FA) and mupirocin, and its relationship to the genetic typing in 34 S. aureus strains, including 6 methicillin-resistant S. aureus (MRSA), isolated from a Chinese hospital. The MIC results showed 27 (79.4%), 1 (2.9%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
3
11
0
Order By: Relevance
“…Interestingly, we also determined that the majority of cfr -positive MRSA isolates harbored optrA , which is in agreement with previous reports suggesting that optrA and cfr coexist ( Li et al, 2016 ; Fan et al, 2017 ). In addition to optrA , our study cfr -positive MRSA isolates also co-carried fexA and ermC , which is also consistent with previous studies ( Liu .X et al, 2017 ). This linked the cotransmission of fexA and ermA-C with cfr gene in diverse plasmids from coagulase-negative Staphylococci as well as Enterobacteriaceae of different origins ( Wang et al, 2012a , 2013 ; Ye et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we also determined that the majority of cfr -positive MRSA isolates harbored optrA , which is in agreement with previous reports suggesting that optrA and cfr coexist ( Li et al, 2016 ; Fan et al, 2017 ). In addition to optrA , our study cfr -positive MRSA isolates also co-carried fexA and ermC , which is also consistent with previous studies ( Liu .X et al, 2017 ). This linked the cotransmission of fexA and ermA-C with cfr gene in diverse plasmids from coagulase-negative Staphylococci as well as Enterobacteriaceae of different origins ( Wang et al, 2012a , 2013 ; Ye et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Liu [39]. Similar results were exhibited by Liu X et al [40], they found that the resistance rate of fusidic acid (2.9%) was much lower than mupirocin (17.6%). According to our study, most of the patients were topically administered with mupirocin rather than fusidic acid, frequent application of mupirocin may contribute to the induction of the drug resistance in our district.…”
Section: Discussionsupporting
confidence: 80%
“…The ST395 lineage expressing GroP-α-GalNAc WTA was unable to undergo HGT with typical S. aureus but may have an increased capacity for acquiring mobile genetic elements, including SCCmec and some virulence genes, from CoNS. ST630 clone has been reported in many previous studies (Yu et al, 2015;Liu et al, 2017), but none of them have described their special WTA phenotypes. We hypothesize that the special tarP-/tarS-/tarM+/tagN+ ST630 clone might serve as a hub for the continuous HGT of multiple MGEs such as antimicrobial resistance and pathogenicity islands (SaPIs) between both S. aureus and CoNS.…”
Section: Discussionmentioning
confidence: 99%